2008
DOI: 10.1097/mpg.0b013e31817b6eea
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and Management of Extrahepatic Portal Vein Obstruction in Children: King's College Hospital Experience

Abstract: The aetiology of EHPVO in the majority of patients remains unknown. Sclerotherapy and banding are effective treatments for bleeding varices with good long-term outcome. Procoagulant state is an infrequent cause of EHPVO in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 34 publications
9
57
1
3
Order By: Relevance
“…As observed in the present study, PVT does not show gender predominance and its more common initial manifestations in children are upper gastrointestinal bleeding and splenomegaly, which corroborates results reported in the literature (1,6,41,47,50,53) . In the present casuistic, upper gastrointestinal bleeding was the main initial clinical manifestation in 52.7% of patients, followed by splenomegaly in 36.4%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As observed in the present study, PVT does not show gender predominance and its more common initial manifestations in children are upper gastrointestinal bleeding and splenomegaly, which corroborates results reported in the literature (1,6,41,47,50,53) . In the present casuistic, upper gastrointestinal bleeding was the main initial clinical manifestation in 52.7% of patients, followed by splenomegaly in 36.4%.…”
Section: Discussionsupporting
confidence: 81%
“…Approximately 79% of the children diagnosed with PVT will show at least one episode of upper gastrointestinal bleeding during their lives (2,41) . In the literature there are few reports on PVT in children and adolescents, being some of them also studies about casuistic descriptions and others about specific characteristics of the disease as thrombophilia (1,17,20,32,43,45,48,53,54,55) . Due to the scarcity of studies in the pediatric age group and the importance of the theme, this study`s objective is to describe the clinical characteristics, diagnosis, evolution and treatment of the portal hypertension in children and adolescents with diagnosis of portal vein thrombosis assisted at the Pediatric Hepatology Clinic of the Hospital das Clínicas of Universidade Federal de Minas Gerais (UFMG), Belo Horizonte, MG, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Protein C activity was low in 20% patients; protein S was low in 2 patients. 16 Antithrombin was normal factor V Leiden mutation were absent in all cases. According to study by Yaccha et al from India, out of 19 children with portal vein thrombosis they had studied alone Protein C deficiency was found in 5 children and combined protein C & elevated anticardiolipin antibody in 3 children.…”
Section: Resultsmentioning
confidence: 99%
“…28 According to Sharma et al factor V leiden and prothrombin gene mutations are infrequent in Indian patients with EHPVO. 16 Out study showed significant deficiency of protein C, protein S and antithrombin III 19.1%, 17% and 12.7% patients respectively out of total 47 patients studied for this.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation